Urgensi Saksi Pelaku yang Bekerjasama (Justice Collaborator) dalam Tindak Pidana Korupsi - Ni Luh Made Dwi Pusparini; A. A. Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2020)
The State of Indonesia appears as a State of Law meaning that State power is exercised according to applicable laws so the law applies to all aspects of social life that lead to the creation of an objective of the law. As a consequence of the weakness of the law in the State of Indonesia there are still a large number of crimes that are developing, including the criminal acts of corruption as one of organized crimes. Not only have corruption crimes developed in Indonesia but also in other countries. As a result, in tackling the emergence of the criminal acts of corruption, it is necessary to have perpetrators cooperating as witnesses with law enforcement authorities in terms of revealing the main perpetrators and others so it has a major influence on the corruption case. Using the normative legal research method, this research examines the urgency of regulating witnesses of collaborating perpetrators in a the criminal act of corruption and the criminal sanctions against witnesses of collaborating perpetrators in criminal acts of corruption. The results show that in positive Indonesian law there are regulations regarding Justice Collaborator in Government Regulation No 71 Article 5 Paragraph (2) of 2000 regulating the rights and legal protection of every witness, criminal reporter / witness who reports. Whereas judges’ considerations in imposing criminal sanctions on justice collaborators in the criminal acts of corruption which are based on Law No. 20 of 2001 related to Law No. 31 of 1999 concerning Eradicating Corruption Crimes and is contained in the Supreme Court Circular No. 4 of 2011 in specific actions regarding Criminal Sanctions namely providing relief in other forms of protection.